Back Cover: Advanced Engineering Materials 5∕2014. Issue 5 (May 2014) - Zschech, Ehrenfried
<x xml:space="preserve">Abstract</x> The Back Cover shows cutter for variable band width. More details can be found in the article by Marco Witte and co‐workers . The picture is take with courtesy of Outokumpu VDM. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>